(untitled) (VIMS Health Science Journal, 2021)
Introduction: Various systemic manifestations and complications have been observed throughout the course of Chronic Obstructive Pulmonary Disease. Out of those manifestations one of the important manifestations is cardiac involvement. The major and well-known cardiac complications of COPD are pulmonary vascular disease and its impact on right ventricular function, higher incidence of myocardial infarction and arrhythmias. These complications correlate inversely with survival. Aim: To study cardiac manifestations in COPD patients and its correlation with severity of the disease. Methodology: This observational study was conducted in the department of medicine at a tertiary care hospital in Solapur, Maharashtra. Data of 80 patients diagnosed and their cardiac status assessed on the basis of clinical findings, radiological changes and spirometry, electrocardiography and echocardiography. All patients were analyzed for cardiac involvement based on symptomatology, ECG and 2D-ECHO results. Results: Out of 80 COPD patients 6 patients were GOLD class 1 (mild), 28 in class 2 (moderate), 36 in class 3 (severe) and 10 patients belonged to GOLD class 4 (very severe). Cardiovascular complications were found in 40 patients out of 80. Of these, pulmonary hypertension was found in 45%, IHD in 30%, cor-pulmonale in 20% and arrhythmias were found in 10% of which supraventricular arrhythmias were seen in 75% and ventricular arrhythmia in25%. Conclusion: Our study concluded that patients with mild to moderate COPD may also have cardiac complications. Due to common symptomatology, they are difficult to diagnose. Hence, it is necessary at the time of initial diagnosis to carry out ECG and 2DECHO for early detection and for better management of these patients.